Effect of physical properties of horticultural substrates on pepper transplant development - Kappel, N.; Terbe, I. (International Journal of Horticultural Science, 2005)
Pepper transplants were grown in trays using 6 different growing media. Trays were filled in a loose and in a compact manner with the 5 different peats and coconut coir. Measurements were made for the most important physical parameters of each single medium studying their effect on transplant development. Results indicated that compaction had had a beneficial effect on the germination of the transplants and on the rate of their development.